Potensi Objek Wisata di Kabupaten Semarang - Darmawan, Soni; Setiawan, Ipang (Universitas Negeri Semarang, 2023)
purpose of the research is to describe and assess the potential tourist attraction, mapping the potential of attractions, and obstacles in developing tourist objects in the City Semarang. The method in this study is a qualitative descriptive triangulation of data collection techniques in the form of observation, interviews and documentation. Analysis is done by data reduction, data presentation, drawing conclusions, and scoring method to determine the potential of attractions.The result of the research shows that the tourism object based on artificial tourism has an advantage compared to nature tourism and cultural tourism. Constraints of synergy between the government, stake holders and Public. The tourism potential that currently exists has not been evenly distributed by the government's role in places tourist attractions as a whole and the community lacks a sense of tourism awareness.The conclusion of the research is the potential of Semarang Regency tourism object natural tourism base, cultural tourism, and artificial tourism. Where artificial base tourist attractions have higher potential, which will later become the leading tourist base in Semarang Regency. High potential tourism objects in Semarang Regency include Bandungan Subdistrict (Candi Gedong Songo), Bawen District (Hortimart Agro Center).Constraints have not been completely involve or not involved the role of the government as a whole and the community lack of awareness of travel. Suggestions should attractions in the city of Semarang be develop, tourism awareness education needs to be held in the community.